Medium modification with bone morphogenetic protein 2 addition for odontogenic differentiation - Cigdem ATALAYIN; Huseyin TEZEL; Taner DAGCI; Nefise Ulku Karabay YAVASOGLU; Gulperi OKTEM (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study was to evaluate whether medium modification improves the odontogenic differentiation of human dental pulp stem cells (DPSC) in vitro and in vivo. DPSC isolated from human impacted third molar teeth were analysed for clusters of differentiation with flow cytometry. Odontogenic differentiation was stimulated by medium modification with the addition of bone morphogenetic protein 2 (BMP2). The expression of dentin sialophosphoprotein, dentin matrix protein 1, enamelysin/matrix metalloproteinase 20 and the phosphate-regulating gene with homologies to endopeptidases on the X chromosome of the cells were analysed with RT-PCR at 7, 14 and 21 days. Then, DPSC were transplanted on the back of immunocompromised mice via a hydroxyapatite tricalcium phosphate scaffold, and the structure of the formed tissue was investigated. The cells were identified as mesenchymal stem cells with a 98.3% CD73 and CD90 double-positive cell rate. The increase in mineralization capacity and expression of human enamel-dentin specific transcripts proportional to the culture period were determined after differentiation. Six weeks after transplantation, an osteo-dentin matrix was formed in the group in which odontogenic differentiation was stimulated, and the odontogenic characteristics of the matrix were confirmed by histological examination and RT-PCR analysis. Odontogenic differentiation of the isolated and characterized human DPSC was improved with medium modification by the addition of BMP2 in vitro and in vivo. The defined medium and applied technique have a potential use for forming reparative dentin in the future, but the effects of the method should be investigated in long-term studies.